دور الطبيعة القانونية للجنسية في تحديد ثنائية المبادئ الناظمة لمركز الدولة و الفرد في تنظيمها - جامع شادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Nationality is a legal system not only for the State but also as a means of determining its population component. For the human community, it is a tool for the international distribution of individuals among political units. States consider nationality to individuals a personal right of those who enjoy it. And it is therefore necessary to attribute the individual to one of the countries of the world and is associated with the nationality association and in his interest and his right to defend this status and the state is obliged to recognize it and respect it. The subject of the study of nationality law brought to the attention of jurists and jurists, especially in determining the legal nature of the nationality association and determining its location between public law and private law, and the consequent consideration of the state as a party in this relationship and the counterparty on the other. We will examine the legal nature of nationality and its role in the dual principles governing the status of the state and the individual in the regulation of nationality. ان الجنسية رابطة قانونية لا تخص الدولة فحسب بل هي وسيلة لتحديد عنصر السكان فيها و هو بالنسبة للمجموعة البشرية أداة لتوزيع الأفراد دوليا بين الوحدات السياسية الدول, تعتبر الجنسية بالنسبة للأفراد حق شخصي لمن يتمتع بها فيتوقف عليها تعيين مقدار الحقوق التي يتمتع بها و يتوقف عليها تعيين القانون الواجب التطبيق, لذا فمن الضرورة أن ينسب الفرد لدولة من دول العالم و يرتبط بها برابطة الجنسية و من مصلحته و حقه ان يدافع عن هذه الصفة و يلزم الدولة الاعتراف له بها و احترامها. جلب موضوع دراسة قانون الجنسية انتباه رجال القانون و الفقه و خاصة في تحديد الطبيعة القانونية لرابطة الجنسية و تحديد موقعها بين القانون العام و القانون الخاص, و ما يترتب على ذلك من اعتبار الدولة كطرف في هذه العلاقة من جهة و الفرد الطرف المقابل في الجهة الأخرى. و سنقوم في بحثنا بدراسة الطبيعة القانونية للجنسية و دورها في ثنائية المبادئ الناظمة لمركز الدولة و الفرد في تنظيم الجنسية.